Liberação controlada do óleo essencial de citronela em matriz têxtil - Bezerra, Fabricio Maestá (2016)
The limiting of use of some finishes in the textile area makes with that new technologies are absorbed by the textile industry for this to become more competitive and can always offer new products that meet the market. Among these, it can highlight the protective oils essences using microcapsules and the formation of complexes with cyclodextrin. There are several microencapsulation techniques, however, this work will be treated in complex coacervation. The microencapsulation by complex coacervation technique is a process in which tiny particles are protected by polymeric material. Complexation already has the protection of the host molecule, whole or in part, by the cyclodextrin. Finishes fabrics with microcapsule or complexescs are among the major allies to develop new textiles. In this context, a large area to be explored is the use of fragrances in textiles, through microencapsulation and complecation. Such techniques offers the possibility of producing new products with many advantages compared to traditional textile products, such as to improve the stability, durability and controlled release of the active compound. However, many studies show only the application of microcapsules in the textile substract, they did not evidence how the release of the encapsulated material occurs in textile matrix, this fact interfers directly in the durability of the finished textile. This work reports since the preparation of microcapsules and complexes until the mechanism and kinetics of controlled release of the microcapsules essential oil of citronella applied in textiles (CO, and WO PES ). This oil is an important mosquito repellent, but its direct application on the fabric is limited due to its rapid volatility. Thus, the protection of oil was gotten by microencapsulation by complex coacervation, with gelatin and Arabic gum as wall material and by complexation using cyclodextrin. The formed microcapsules and complexes were evaluated by scanning electron microscopy (SEM), optical microscopy, Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG), performance (UV-VIS), Dynamic light scattering (DLS). After, the microcapsules was apllied in cotton, wool and polyester fabrics (CO, WO, PES) by pad-dry and, after, it became the assessment of finishes using spectroscopy in the infrared attenuated total reflectance with (FTIR-ATR). finally it was made, the controlled release of microcapsules on the tissues in vitro. Thus, adjustments are performed to determine the constants of Higuchi and Korsmeyer and Peppas. It can observer the realization of the microcapsules, the their efficiency, size distribution, as well as the tissue application. Also it was found that the release was directly influenced by the type of fiber, the microcapsules apply in WO and PES articles always presented Fickian mechanism, while the kinetic adjustments made to the CO presented at first Fickian diffusion and, after becomes If anomalous.To end it , the control release knowledge of citronella oil is fundamental for the creation/development of more durable smart textiles.